ANALISIS DAMPAK KEPUASAN PELANGGAN DALAM HUBUNGAN ANTARA ORIENTASI PELAYANAN DAN KUALITAS PELAYANAN TERHADAP LOYALITASPELANGGAN PT TIKI CABANG MIMIKA - Ayu Febbriyanti; Wulandari; Siske Tontong (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to determine and analyse the impact of customer satisfaction in the relationship between service orientation and service quality on customer satisfaction. To achieve this objective, an associative method was used, which is a method used to describe the relationship between one variable and another. The results of this study indicate that service orientation and service quality have a positive and significant influence on customer satisfaction. Similarly, service orientation and service quality have a positive and significant influence on customer loyalty. However, customer satisfaction does not have a significant influence on customer loyalty. Additionally, service orientation and service quality do not have a significant influence on customer loyalty through the mediation of customer satisfaction.